Odpowiedź :
Odpowiedź:
32) 0,75 + 5x = 4,75
5x = 4,75 - 0,75
5x = 4 /: 5
x = 0,8
Spr. : L = 0,75 + 5x = 0,75 + 5 • 0,8 = 0,75 + 4 =
= 4,75
P = 4,75
L = P
33) 2x - 0,3 = 5,3
2x = 5,3 + 0,3
2x = 5,6 /: 2
x = 2,8
Spr. : L = 2x - 0,3 = 2 • 2,8 - 0,3 = 5,6 - 0,3 = 5,3
P = 5,3
L = P
34) 7z + 6 + 4z = 9 - 2z + 10
7z + 4z + 2z = 9 + 10 - 6
13z = 13 /: 13
z = 1
Spr. : L = 7z + 6 + 4z = 7 • 1 + 6 + 4 • 1 = 7 + 6 + 4 =
= 13 + 4 = 17
P = 9 - 2z + 10 = 9 - 2 • 1 + 10 = 9 - 2 + 10 = 7 + 10 =
= 17
L = P
35) -6w + 13 - 2w = 13 - 5w + 15
-6w - 2w + 5w = 13 + 15 - 13
-3w = 15 /: (-3)
w = -5
Spr. : -6w + 13 - 2w = -6 • (-5) + 13 - 2 • (-5) =
= 30 + 13 - (-10) = 43 - (-10) = 53
P = 13 - 5w + 15 = 13 - 5 • (-5) + 15 = 13 - (-25) + 15 =
= 38 + 15 = 53
L = P
36) 7x - 18 + 3x - 28 - 5x - 8x = 2x
7x + 3x - 5x - 8x - 2x = 18 + 28
-5x = 46 /: (-5)
x = - 9 1/5
Spr. : L = 7x - 18 + 3x - 28 - 5x - 8x =
= 7 • (-9 i 1/5) - 18 + 3 • (-9 i 1/5) - 27 - 5 • (-9 i 1/5) - 8 • (-9 i 1/5) = 7 • (-46/5) - 18 + 3 • (-46/5) - 27 - 5 • (-46/5) - 8 • (-46/5) =
= -322/5 - 18 - 138/5 - 28 + 230/5 + 368/5 = -64 i 2/5 - 18 - 27 i 3/5 - 28 + 46 + 73 i i 3/5 = -138 + 119 i 3/5 = -18 i 2/5
P = 2x = 2 • (-9 i 1/5) = 2 • (-46/5) = -92/5 =
= -18 i 2/5
L = P
37) -16 + 15x + 4x - 22 = 8x - 27
15x + 4x - 8x = -27 + 16 + 22
11x = 11 /: 11
x = 1
Spr. : L = -16 + 15x + 4x - 22 = -16 + 15 • 1 + 4 • 1 - 22 = -16 + 15 + 4 - 22 = -1 + 4 - 22 = 3 - 22 = -19
P = 8x - 27 = 8 • 1 - 27 = 8 - 27 = -19
L = P
Pozdrawiam.